Heritability and environmental influences on the onset of aortic valve sclerosis: a twin population study. (3rd October 2022) - Poggio, P; Myasoedova, V; Ravani, A; Frigerio, B; Gripari, P; Mantegazza, V; Valerio, V; Moschetta, D; Massaiu, I; D'Ippolito, C; Baldassarre, D; Tamborini, G; et al.
Abstract: Background: Aortic valve sclerosis (AVSc) is the earliest manifestation of a life-threatening cardiovascular disorder, namely aortic valve stenosis (AS). AVSc is also recognized as a red flag linked to worse cardiovascular outcomes in high-risk coronary artery disease patients. However, the genetic background of AVSc is still unknown. Purpose: To examine whether the heritability and environmental contributions play a role in the onset of AVSc using a sample of Italian twins. Methods: The present study is based on the classical twin design. Twins, aged 50 to 70 years, already enrolled in the Italian Twin Register, were contacted and invited to undergo a clinical, echocardiographic, and complete carotid artery ultrasound examination at the our Center, between July 2017 and December 2021. The presence of AVSc was recognized as non-uniform thickening with or without spotty calcified areas of the aortic valve leaflets without a significant transvalvular gradient (maximum aortic velocity <2.5 m/s). Twin zygosity was assessed through a questionnaire on physical similarity during childhood, known to be ∼95% accurate. Tetrachoric twin correlations by zygosity were estimated with Mx Software using liability threshold saturated models and incorporating age as a covariate. Liability-threshold structural equation modelling was performed to decompose the phenotypic variance into contributions due to additive genetic (A), common environmental (C), and unique environmental (E) effects. Results: A total of 216 adult twins (66 monozygotic, MZ and 42 dizygotic pairs, DZ; mean age 59.9±6.2) were enrolled in the study. The estimated prevalence rate of AVSc in the total sample was 29.2%. As significant sex differences were detected (males 45.2% and females 22.7%, p<0.01), the additional twin analyses were performed as intra-sex analyses. Females showed a greater tetrachoric correlation in MZ twins (r=0.37) compared to DZ twins (r=0.23), suggesting the existence of a genetic influence. Genetic factors, under the best (AE) model, accounted for 38% of the variance in liability to AVSc with the remaining contribution due to unique environmental influences (E = 62%). The contribution of the common environment (C) to the goodness of fit was negligible. The male group was too small for statistical calculation. Conclusion: To our knowledge, the present study is the first to document the involvement of genetic factors in the development of AVSc. Our data also warrant further studies to both validate the findings obtained and to better explore the heritability of AVSc. Furthermore, our results provide a first evidence that an echocardiographic screening in individuals with relatives affected by AVSc has a scientific rational basis. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Italian Ministry of Health